Utility and Interobserver Agreement of Ultrasound Elastography in the Detection of Malignant Thyroid Nodules in Clinical Care - Merino, S. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Malignancy correlates with hardness of tissues and US elastography can potentially analyze the stiffness of lesions. Our aim was to evaluate the utility of US elastography in the detection of malignant nodules and to investigate interobserver agreement with this technique. MATERIALS AND METHODS: One-hundred three consecutive patients with 106 thyroid nodules were examined prospectively with conventional B-mode sonography and real-time US elastography. All patients were referred for FNAB. Conventional B-mode sonography and US elastographic examinations were performed, and images were separated and independently interpreted by 2 radiologists blinded to pathologic results. US elastogram evaluation was based on a simplified classification of stiffness based on gray-scale patterns, tumor size compared with B-mode, and margins. Interobserver agreement was studied. FNAB was used as the reference standard for the diagnosis of benign nodules, but histopathologic evaluations were performed when results suspicious for malignancy or malignant results were obtained on FNAB as well as in indeterminate lesions. RESULTS: In our study, pattern of stiffness based on gray-scale and classification proposed were statistically significant and predicted malignancy with 100% sensitivity and 40.6% specificity. Tumor size when compared with B-mode images or margins was not statistically significant in our study. No false-negatives were found, and an NPV of 100% was seen. Interobserver agreement for US elastography was excellent in our study, with a κ index of 0.82 (95% CI). CONCLUSIONS: We believe that US elastography is a promising technique that can assist in the evaluation of thyroid nodules and can potentially diminish the number of FNAB procedures needed. We believe that it may be useful to introduce US elastography into routine clinical practice.